Mass-degenerate Higgs bosons near 125 GeV in the NMSSM under current experimental constraints - Liangliang Shang; Pengqiang Sun; Zhaoxia Heng; Yangle He; Bingfang Yang (European Physical Journal C: Particles and Fields, 2020)
Abstract The observed Higgs signal at the Large Hadron Collider (LHC) may be derived from the two mass-degenerate resonances. We investigate this scenario in the Next-to-Minimal Supersymmetric Standard Model (NMSSM) in which both the two lightest CP-even Higgs bosons have masses around 125 GeV. We perform a comprehensive scan over the parameters in the NMSSM considering the current experimental constraints, especially the constraints from dark matter direct detection. The surviving samples are featured with relatively small $$μ $$ μ and large $$\tan β $$ tanβ . The samples with large deviation of double ratios have large mixing between doublet field and singlet field.